Nuclear β catenin as a potential prognostic and diagnostic marker in patients with colorectal cancer from Hong Kong. Issue 6 (26th November 2003) - Wong, S C C; Lo, E S F; Chan, A K C; Lee, K C; Hsiao, W L
Abstract : Aims: To study the expression of nuclear β catenin in patients with colorectal cancer, colorectal adenoma, and colorectal polyps to elucidate its role in carcinogenesis, and its potential for prognosis and diagnosis. Methods: The expression of nuclear β catenin was studied by immunohistochemistry using paraffin wax embedded specimens. Sixty specimens each of colorectal carcinoma, colorectal adenoma, colorectal polyp, and normal colorectal specimens were analysed. The potential for prognosis was assessed by correlating nuclear β catenin expression in 60 and 75 patients with colorectal cancer with lymph node metastasis and survival, respectively. The diagnostic capacity was explored by comparing nuclear β catenin expression in 60 patients with colorectal cancer with other cytokeratin 20 (CK20) positive adenocarcinomas, namely: 30 colonic mucinous adenocarcinomas, 30 gastric adenocarcinomas, 27 pancreatic adenocarcinomas, and 12 ovarian mucinous adenocarcinomas. Results: Nuclear β catenin expression was highly associated with progression of colorectal tissue from normal epithelial tissue, polyps, adenomas, to carcinomas ( r  =  0.875; p < 0.0001). Nineteen patients with colorectal adenoma who subsequently developed colorectal carcinoma had higher nuclear β catenin expression than those with colorectal adenomas alone (p < 0.0001). Moreover, those patients with colorectal cancer and high nuclear β catenin expression had a higher incidence of lymph node metastasis (χ 2  =  16.99; p < 0.005) and shorter overall survival (p < 0.0001). Finally, nuclear β catenin expression in colorectal adenocarcinomas was significantly higher than in other CK20 positive adenocarcinomas. Conclusions: Nuclear β catenin expression is a potential prognostic factor in patients with colorectal cancer, and together with CK20, it could be used to identify colorectal carcinoma in the Hong Kong population.